2006
DOI: 10.1097/01.opx.0000218432.52508.10
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion Cell Loss and Age-Related Visual Loss: A Cortical Pooling Analysis

Abstract: Purpose-To evaluate the ability of the cortical pooling model to predict the effects of random, mild ganglion cell loss, we compared the predictions of the model with the age-related loss and variability in achromatic and chromatic contrast sensitivity.Methods-The relative sensitivity to small (0.5°) and large (3.0°) stimuli was compared in older (mean = 67 years, n = 27) and younger (mean = 23 years, n = 32) adults. Contrast sensitivity for modulations along the luminance, equiluminant L-cone, and equiluminan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 55 publications
5
20
0
Order By: Relevance
“…In a monkey model of glaucoma, RGC morphological changes start with dendritic alterations followed by axon thinning and finally somal shrinkage (Weber et al, 1998). Evidence of retinal ganglion cell shrinkage in monkey and human (Morgan et al, 2000;Morgan, 2002) as well as analysis of patient functional data (Pearson et al, 2006) have combined to cast doubt on previous reports of selective large ganglion cell loss. Although dendritic alterations were not examined in this study , Jakobs et.…”
Section: Neun-positive Cells Shrink In Dba/2mentioning
confidence: 99%
“…In a monkey model of glaucoma, RGC morphological changes start with dendritic alterations followed by axon thinning and finally somal shrinkage (Weber et al, 1998). Evidence of retinal ganglion cell shrinkage in monkey and human (Morgan et al, 2000;Morgan, 2002) as well as analysis of patient functional data (Pearson et al, 2006) have combined to cast doubt on previous reports of selective large ganglion cell loss. Although dendritic alterations were not examined in this study , Jakobs et.…”
Section: Neun-positive Cells Shrink In Dba/2mentioning
confidence: 99%
“…The assumption that detection is determined by responsiveness of an individual ganglion cell would lead one to expect that perimetric sensitivity for this stimulus would be relatively unaffected by modest amounts of ganglion cell loss 22 . By comparison, assessment of cortical pooling effects on spatial summation concluded that sensitivity to the size III stimulus declines with even modest amount of ganglion cell loss, 21,23,24 and that this is seen even for the much larger stimuli used in frequency‐doubling perimetry 25 …”
Section: Psychophysical Factors Influencing the Structure–function Rementioning
confidence: 99%
“…21 The assumption that detection is determined by responsiveness of an individual ganglion cell would lead one to expect that perimetric sensitivity for this stimulus would be relatively unaffected by modest amounts of ganglion cell loss. 22 By comparison, assessment of cortical pooling effects on spatial summation concluded that sensitivity to the size III stimulus declines with even modest amount of ganglion cell loss, 21,23,24 and that this is seen even for the much larger stimuli used in frequency-doubling perimetry. 25 Cortical pooling of ganglion cell responses can be characterized in terms of multiple spatial mechanisms or multiple cortical detectors with peak responses at different spatial frequencies, 26 where Ricco's area is determined by the spatial mechanism with the greatest sensitivity to small luminance increments.…”
Section: Structure-function Relationshipmentioning
confidence: 99%
“…13 Studies in Australia 14,15 USA 16 show that the prevalence of the disease increases steadily with each decade over the age of 55. The number of retinal ganglion cells is known to decrease gradually with age even in normal human subjects 17,18 and animal models. 19 This decline in ganglion cell number will reduce neural redundancy and impact on vision in older age.…”
Section: Ageingmentioning
confidence: 99%